Financial Performance in Manufacturing Company with Multiple Linier Regression and MARS - Moch Bisyri Effendi (University of Merdeka Malang, 2018)
The purpose of this research is to analyze the influence of environmental disclosure and environmental performance on economic performance with firm size as a control variable. The environmental disclosure was measured by GRI index, environmental performance measured by PROPER index, firm size measured by ln total assets and economic performance measured by economic performance index. The sample of this study consists of 32 companies listed on the IDX 2013-2016. The criteria of the research sample are manufacturing companies that follow PROPER index, issuing financial statements with rupiah currency, publish a complete annual report. The results of this study inform that the performance of Multivariate Adaptive Regression Spline (MARS) is better than multiple linear regression. The result of multiple linear regression informs that not all classical assumption requirements are fulfilled. This results in a non-significant regression model, small R-square, and many predictor variables have no effect on response variables. MARS is one of the alternative methods to overcome the lack of multiple linear regression methods. MARS is not a requirement with classical assumptions because it includes one of the non-parametric regressions. MARS results informed that the MARS model is significant, R-square is large and the variables that affecting the economic performance are environmental disclosure and environmental performance while the most influential is the environmental performance.JEL Classification: F64; G30DOI: https://doi.org/10.26905/jkdp.v22i1.1609